INDÍCIOS DE CONSTITUCIONALISMO ABUSIVO NO BRASIL DURANTE O GOVERNO BOLSONARO (2019-2022) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
Since the election of Donald Trump to the US presidency, several theorists have pointed out the existence of a crisis in liberal constitutional democracies. With this, several concepts were rescued to try to understand the rise of far-right populism on a global scale, among which: constitutional hardball, constitutional rot, constitutional erosion and, of particular importance for this work, abusive constitutionalism, theorized by David Landau. This article aims to analyze the application of this concept to the Brazilian reality, based on the case study of three situations that occurred during Jair Bolsonaro's mandate, between the years 2019 and 2022: the interpretation of article 142 of the 1988 Federal Constitution made by its supporters, the attacks perpetrated by the administration against the Judiciary and the decision to forcefully withdraw Venezuelan diplomats from the national territory. The research also intends to demonstrate how the Federal Supreme Court acted in each of these cases. To this end, we opted for the methodological choice of, initially, with the contributions of the bibliographical review, reviewing the main concepts regarding the phenomenon of abusive constitutionalism and then seeking their application in concrete cases of the national reality. The results found were that, although Brazil has gone through episodes of abusive constitutionalism, there is no evidence that there is any form of structural abusiveness in national constitutionalism. Therefore, Brazilian democracy has shown itself capable of resisting the authoritarian attacks of recent years.